Les coulisses du sublime - Emmanuel Grimaud (Ateliers d'Anthropologie)
Cinema is engaged from its origins in a frantic race to make physically impossible actions visually plausible by camouflaging their conditions of application. Who is at the origin of what? Is there a method and which one? Was the actor supported by machines or by cables? Did he perform the stunt himself? etc. But the impossible act which the set contends to achieve is never simply due to the actor, the technicians or the camera. It is also never completely reducible to special effects. Both physical performance (but not only), a strand machinic and largely collective (or distributed), the effect of virtuosity in movies is also still incomplete without the perception of an audience who gives a final continuity to the stunt. By examining how stunts are done, camouflaged and how they confuse the viewer on their sources and processes, this article explores the challenges of this hybrid and complicated virtuosity that takes the optically act away from its material conditions of performance.